Antimicrobial resistance in Streptococcus pneumoniae: a retrospective analysis of emerging trends in the United Arab Emirates from 2010 to 2021 - Senok, Abiola; Thomsen, Jens; Abdulrazzaq, Najiba M., The UAE AMR Surveillance Consortium; Menezes, Godfred Antony; Ayoub Moubareck, Carole; Everett, Dean (Frontiers in Public Health, 2023)
Introduction Although pneumococcal conjugate vaccines (PCV) have been effective in reducing the burden of Streptococcus pneumoniae infections, there is a paucity of data on the relationship with antimicrobial resistance (AMR) trends in the Arabian Gulf region. This study was carried out to assess S. pneumoniae resistance trends in the United Arab Emirates (UAE) where PCV-13 vaccination was introduced in 2011. Methods Retrospective analysis of S. pneumoniae demographic and microbiological data collected as part of the national AMR surveillance program from 2010 to 2021 was carried out. A survey of reporting sites and hand searching of annual reports of local health authorities was carried out to identify data on S. pneumoniae serotypes as this is not included in the AMR surveillance database. Results From 2010 to 2021, 11,242 non-duplicate S. pneumoniae isolates were reported, increasing from 324 in 2010 to 1,115 in 2021. Factoring in annual increment in the number of surveillance sites, the number of isolates per site showed an upward trajectory from 2015 to 2018 and declined in 2020 with the onset of the pandemic. The majority of isolates (n/N = 5,751/11,242; 51.2%) were from respiratory tract specimens with 44.5% (n/N = 2,557/5,751) being nasal colonizers. Up to 11.9% (n/N = 1,337/11,242) were invasive pneumococcal disease (IPD) isolates obtained from sterile site specimens including blood (n = 1,262), cerebrospinal (n = 52), pleural (n = 19) and joint (n = 4) fluid; and were predominantly from pediatric patients. The downward trend for amoxicillin and for penicillin G at the non-meningitis and meningitis as well as oral penicillin breakpoints was statistically significant. In contrast, increasing trends of resistance were seen for levofloxacin, moxifloxacin, trimethoprim/sulfamethoxazole and erythromycin. IPD and non-IPD isolates showed similar demographic and AMR trends. None of the surveillance sites carried out S. pneumoniae serotyping and handsearching of annual reports did not yield this information. Conclusion The increasing trend of pneumococcal disease and AMR with emergence of isolates with MDR phenotype despite is of concern. In the absence of S. pneumoniae serotyping the role of non-vaccine serotypes in driving this pattern remains unknown. There is an urgent need for serotype, genomic and AMR surveillance of S. pneumoniae isolates in the UAE.